2013
DOI: 10.1155/2013/696274
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Associated with Influenza in Tropics, State of São Paulo, Brazil, from 2002 to 2011: The Pre-Pandemic, Pandemic, and Post-Pandemic Periods

Abstract: The impact of the seasonal influenza and 2009 AH1N1 pandemic influenza on mortality is not yet completely understood, particularly in tropical and subtropical countries. The trends of influenza related mortality rate in different age groups and different outcomes on a area in tropical and subtropical climate with more than 41 million people (State of São Paulo, Brazil), were studied from 2002 to 2011 were studied. Serfling-type regression analysis was performed using weekly mortality registries and virological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 18 publications
3
29
1
4
Order By: Relevance
“…Our estimated influenza‐associated in‐hospital mortality was similar to that reported previously in the region, except for the lower mortality rates we estimated among adults aged >64 years 6, 12, 13. Our rates among children aged <5 years were also lower than those of a global meta‐analysis using different methodology,1 whereby 4·9 children per 100 000 died from influenza‐associated severe acute lower respiratory infection (ALRI) in developing countries.…”
Section: Discussionsupporting
confidence: 83%
“…Our estimated influenza‐associated in‐hospital mortality was similar to that reported previously in the region, except for the lower mortality rates we estimated among adults aged >64 years 6, 12, 13. Our rates among children aged <5 years were also lower than those of a global meta‐analysis using different methodology,1 whereby 4·9 children per 100 000 died from influenza‐associated severe acute lower respiratory infection (ALRI) in developing countries.…”
Section: Discussionsupporting
confidence: 83%
“…However, pandemic-related mortality rates were higher in the 5-19-year age group and lower in the >45-year age group compared with typical seasons. Other studies have reported overall lower mortality rates associated with the first year of circulation of the 2009 pandemic virus, compared with that of seasonal influenza, but have found a higher disease burden for children and young adults (4,(21)(22)(23)(24)(25). Our estimates are similar to the lower-bound estimates for South Africa from a global influenza A(H1N1)pdm09 mortality model (26).…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, a higher percent positivity for influenza was reported among the older age‐group as compared to the younger age‐groups, which provides further evidence of the greater burden in this age‐group. This pattern is maintained for all viral subtypes; however, the differences tend to decrease with influenza A(H1N1) perhaps due to the published finding that influenza(H1N1)pdm09 affects younger adults more than older ones due to absence of immune‐protection against this virus (USA, Mexico, Brazil, four European countries) 24, 25, 26…”
Section: Discussionmentioning
confidence: 98%
“…This pattern is maintained for all viral subtypes; however, the differences tend to decrease with influenza A(H1N1) perhaps due to the published finding that influenza(H1N1)pdm09 affects younger adults more than older ones due to absence of immune-protection against this virus (USA, Mexico, Brazil, four European countries). [24][25][26] Our estimates for persons aged 65 years and older are greater than those reported in an analysis from Central America using the (170-1033 influenza-associated hospitalizations per 100 000 persons-years). 17 Our estimates found among children under 5 years of age are similar to the global meta-analysis for countries in the Americas (71 influenza-associated hospitalizations per 100 000 persons-years) 27 and lower than the estimates from Central American countries (113 influenza-associated hospitalization per 100 000 persons-year).…”
Section: Discussionmentioning
confidence: 99%